Filial responses as predisposed and learned preferences: Early attachment in chicks and babies - Di Giorgio, Elisa; Loveland, Jasmine L.; Mayer, Uwe; Rosa-Salva, Orsola; Versace, Elisabetta; Vallortigara, Giorgio (Behavioural brain research, 2017)
•Predispositions orient newborn babies and chicks towards animate objects.•Subcortical/subpallial structures may be sufficient to support social predispositions.•Social Behaviour Network areas might be involved in unlearnt social behaviours.•Hormones facilitate preferences for predisposed stimuli and social attachment.•Social predispositions are impaired in newborns at high genetic risk for autism. To what extent are filial responses the outcome of spontaneous or acquired preferences? The case of domestic chicks illustrates the connection between predisposed and learned knowledge in early social responses. In the absence of specific experience, chicks prefer to approach objects that are more similar to natural social partners (e.g. they prefer face-like configurations, biological motion, self-propelled objects and those that move at variable speed). Spontaneous preferences are complemented by filial imprinting, a powerful learning mechanism that enables chicks to quickly learn the features of specific social partners. While neurobiological studies have clarified that the substrates of spontaneous and learned preferences are at least partially distinct in chicks, evidence shows that spontaneous preferences might orient and facilitate imprinting on animate stimuli, such as the mother hen, and that hormones facilitate and strengthen preferences for predisposed stimuli. Preferences towards animate stimuli are observed in human neonates as well. The remarkable consistency between the perceptual cues attended to by newborn babies and naïve chicks suggests that the attentional biases observed in babies are unlikely to result from very rapid post-natal learning, and confirms that research on precocial species can inform and guide human infant research with regards to both typical and atypical development. This has potentially important biomedical implications, opening new possibilities for the early detection of subjects at risk for autism spectrum disorders. We show how the parallel investigation of predispositions in naïve chicks and human infants, both benefiting from contact with social partners since the beginning of life, has greatly improved our understanding of early responses to social stimuli at the behavioural and neurobiological level.